Influence of Product Quality, Price and Digital Marketing Against Decision Purchase Motorcycle Yamaha in Mayaraya Motor Makassar - alfianto , Andi Alfianto; Sofian, Muhammad Fahimi Bin; Hasan, Hamida; Alimuddin, Firman (AhInstitute of Research and Community Service (LP2M) Institute of Social Sciences and Business Andi Sapada, 2023)
The purpose of this study was to determine the effect of product quality, price and digital marketing on purchasing decisions for Yamaha motorbikes at Maharaya Motor Makassar City The data analysis method used is validity test, reliability test, multiple linear regression, partial tests, simultaneous test and coefficient of determination to find out the hypothesis in this study. The results of the analysis of the data obtained by the researchers indicates that Product Quality (Xı) does not partially influence the Purchase Decision of yamaha Maharaya Motor Makassar City (1.572 <2.003) and a significant level (0.122 > 0.05). Price (X2) has a partial effect on purchasing decisions for Yamaha motorbikes at Maharaya Motor Makassar City (2.581 > 2.003) and significant (0.012 <0.05). Digital Marketing (X3) has no significant effect partially on the purchasing decision of yamaha Maharaya Motor Makassar City (-0.154 <2.003) and significant (0.878 > 0.05). Product quality, price and digital marketing have a significant simultaneous effect on purchasing decisions for Yamaha motorbikes at Maharaya Motor Makassar City (2.892 > 2.77). The R Square or R Square value obtained is 0.134, meaning 13.4% influence product quality, price and digital marketing on purchasing decisions for Yamaha motorbikes at Maharaya Motor Makassar City, while the remaining 86.6% is influenced by other variables not examined, such as promotion, location, purchase satisfaction and so on.